2023
DOI: 10.1097/ede.0000000000001609
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Opioid and Benzodiazepine Poisoning Deaths After Cannabis Legalization in the US: A County-level Analysis, 2002–2020

Abstract: Background: Cannabis legalization for medical and recreational purposes has been suggested as an effective strategy to reduce opioid and benzodiazepine use and deaths. We examined the county-level association between medical and recreational cannabis laws and poisoning deaths involving opioids and benzodiazepines in the US from 2002 to 2020. Methods: Our ecologic county-level, spatiotemporal study comprised 49 states. Exposures were state-level implementation of medical and recreational cannabis laws and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…However, there was an increase in overdose deaths involving prescription opioids between years 2 and 4 after medical cannabis law implementation, suggesting potential co-use of cannabis and opioids that was not always under clinical supervision. Meanwhile, our finding indicating a possible association between recreational cannabis laws and reduced synthetic opioid deaths may suggest that users of fentanyl (and other synthetic opioids) switched to recreational cannabis or reduced use of other sedating substances, such as benzodiazepines, that can increase overdose risk when mixed with fentanyl . It is also possible that recreational cannabis laws make cannabis more available and thus reduce initiation of opioid use.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…However, there was an increase in overdose deaths involving prescription opioids between years 2 and 4 after medical cannabis law implementation, suggesting potential co-use of cannabis and opioids that was not always under clinical supervision. Meanwhile, our finding indicating a possible association between recreational cannabis laws and reduced synthetic opioid deaths may suggest that users of fentanyl (and other synthetic opioids) switched to recreational cannabis or reduced use of other sedating substances, such as benzodiazepines, that can increase overdose risk when mixed with fentanyl . It is also possible that recreational cannabis laws make cannabis more available and thus reduce initiation of opioid use.…”
Section: Discussionmentioning
confidence: 81%
“…These results contrast with recent studies that suggested that recreational and medical cannabis legalization are associated with reductions in opioid prescriptions 21 , 22 and medical cannabis legalization is associated with an increase in opioid mortality. 14 , 15 , 16 , 17 These conflicting findings may arise from many factors, including differences in the study cohorts and periods examined, methods of defining the exposures and outcomes of interest, and empirical approaches used to evaluate these laws.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 A report in 2018 concluded that medical marijuana legalization was associated with a 30% reduction in Schedule III opioid Medicaid prescriptions. 45 Two county-level studies in states that allowed marijuana dispensaries to operate had lower opioid-mortality rates in counties with medical and recreational dispensaries, 46,47 albeit the county-level methodology utilized has been negatively critiqued. 7,48…”
Section: Discussionmentioning
confidence: 99%
“…44 A report in 2018 concluded that medical marijuana legalization was associated with a 30% reduction in Schedule III opioid Medicaid prescriptions. 45 Two county-level studies in states that allowed marijuana dispensaries to operate had lower opioid-mortality rates in counties with medical and recreational dispensaries, 46,47 albeit the county-level methodology utilized has been negatively critiqued. 7,48 At the national level, an update of aforementioned studies by other investigators indicates that legal medical marijuana is associated with higher opioid mortality, particularly when available through retail dispensaries, and that recreational marijuana may be correlated with greater death rates relative to the counterfactual of no legal cannabis.…”
Section: Prior Studies Of Marijuana Legalization's Effect On Opioid M...mentioning
confidence: 99%